Quiz 19 Flashcards
Assume ∀x ∀y P(x,y)
Assumption
∀y P(x,y)
Universal Instantiation
P(x,x)
Universal Instantiation
∀x P(x,x)
Universal Generalization
∴ ∀x ∀y P(x,y) → ∀x P(x,x)
Derivation
Assume ∀x ¬P(x)
Assumption
Assume ∃x P(x)
Assumption
P(x)
Existential Instantiation
∀x ¬P(x)
Copy
¬P(x)
Universal Instantiation
P(x)
Copy
P(x) ∧ ¬P(x)
Conjunction
0…p ∧ ¬p ≡ 0…∴ ∃x P(x) → 0
Derivation
¬∃x P(x)
Contradiction
∴ ∀x ¬P(x) → ¬∃x P(x)
Derivation
Assume ¬∃x P(x)
Assumption
Let x be arbitrary…Comment….Assume P(x)
Assumption
∃x P(x)
Existential Generalization
¬∃x P(x)
Copy
∃x P(x)..∧ ¬∃x P(x)
Conjunction
0…p ∧ ¬p ≡ 0…∴ P(x) → 0
Derivation
¬P(x)
Contradiction
∀x ¬P(x)
Universal Generalization
∴ ¬∃x P(x) → ∀x ¬P(x)
Derivation
∀x ¬P(x) → ¬∃x P(x)
Copy
(¬∃x P(x) → ∀x ¬P(x)) ∧ (∀x ¬P(x) → ¬∃x P(x))
Conjunction
(¬∃x P(x) ↔ ∀x ¬P(x))…(a ↔ b) ≡ (a → b) ∧ (b → a)
∀P (¬∃x P(x) ↔ ∀x ¬P(x)).
Universal Generalization
Assume ∀x P(x)
Assumption
P(0)
Universal Instantiation
∃x P(x)
Existential Generalization
∴ ∀x P(x) → ∃x P(x)
Derivation